The Structure of the Cusp Diamagnetic Cavity and Test Particle Energization in the GAMERA Global MHD Simulation. Issue 12 (17th December 2021) - Burkholder, B. L.; Nykyri, K.; Ma, X.; Sorathia, K.; Michael, A.; Otto, A.; Merkin, V.
Abstract: Electrons with energies ≥40 keV can be found at low density in many different regions of Earth's magnetosphere. A litany of fundamental questions in space physics have focused on the acceleration mechanism of these particles, given that the sources of plasma are the relatively cool ionosphere and solar wind (∼1–100s eV). Upgraded global solar wind‐magnetosphere simulations which can resolve mesoscale dynamics have the ability to enhance our understanding of these high energy particles. This is because the energization of particles often takes the form of a sequence of discrete steps, potentially occurring in different regions of the magnetosphere and due to both meso‐ and global‐scale processes. First, brief results are presented from the Grid Agnostic MHD for Extended Research Applications (GAMERA) global simulation on the structure of the cusp diamagnetic cavity for northward and southward IMF. Then, the Conservative Hamiltonian Integrator for Magnetospheric Particles (CHIMP) framework, with both guiding center and full Lorentz integrators, evolves necessary parameters such as the energy and pitch angle of electron test particles to investigate particle acceleration inside the cavity, as well as the ultimate fate of electrons accelerated inside the cavity. The simulation shows that particles can gain ≥ 10 keV inside the cavity and subsequently leak into the magnetosheath or onto dipolar field lines where they execute different types of bounce motion. The distribution of test particles initialized inside the cavity is compared with Magnetospheric Multi‐Scale (MMS) observations. Key Points: The structure of the cusp diamagnetic cavity depends strongly on interplanetary magnetic field direction As described by MHD only, electron test particles in a diamagnetic cavity can gain 10s of keV Accelerated electrons can escape from the cavity to open magnetosheath field lines